The handbook of discourse analysis - Tannen, Deborah; Hamilton, Heidi Ehernberger; Schiffrin, Deborah (Wiley Blackwell, 2015)
The second edition of the highly successful Handbook of Discourse Analysis has been expanded and thoroughly updated to reflect the very latest research to have developed since the original publication, including new theoretical paradigms and discourse-analytic models, in an authoritative two-volume set. Twenty new chapters highlight emerging trends and the latest areas of research Contributions reflect the range, depth, and richness of current research in the field Chapters are written by internationally-recognized leaders in their respective fields, constituting a Who's Who of Discourse An.- Resumé vydavatel
Keywords: diskurzivní analýza; discourse analysis; elektronické knihy; příručky; sborníky; electronic books; handbooks and manuals; papers of several authors